Direitos humanos como ordenadores da atividade econômica no Brasil - Oliveira, Jeferson Sousa (2019)
The exercise of economic activity has always proved important for the development of society, gaining new contours as the market evolved. The intensification of human integration has made the market gain international dimensions, expanding business relations and encouraging the search for capital. Along with the strengthening of business relations, the market began to demand the sacrifice of human well-being under the pretext of providing economic development for the poorest, which has not occurred until the present day. Failure to comply with this promise has raised many questions, since in addition to keeping several states immersed in poverty, the market has reaped the well-being of millions of people around the world, including Brazil, which has sought through its main normative provisions preserve the dignity of the Brazilian people, especially in the face of the abuses of economic power and the exploitation of internal market failures. In this context, through the hypothetical-deductive method and historical-normative analysis, it is sought, based on a legal-economic view, to highlight some of the reasons that prevent Brazil from achieving full socioeconomic development, demanding an immediate change of values social and market conditions, so as to build a better society founded on social justice and the reduction of financial inequalities, based on respect for human rights, constitutional provisions and effective corporate social responsibility.